Penjaminan Kualitas Pengukuran Tegangan dari Multifunction Calibrator sebagai Standar Pengukuran di Badan Standardisasi Nasional (SNSU-BSN) - Nibras Yayienda; Retno Wigajatri Purnamaningsih (Postgraduate, University of Mataram, 2022)
Based on ISO 17025: 2017 clause 7.7, SNSU BSN as the peak of traceability must have quality assurance for measurement results, this is in line with the peer review result of Electrical Laboratory in 2017 and 2019 that suggest doing an intermediate check to support the quality of the measurement results issued by the Electrical Laboratory of SNSU – BSN. The method used method in this research is intermediate check including establishing the control line from the initial data and examining it every month over the year. The out-of-control measurement result will be analyzed more deeply using F-test and T-Test. The result of this test will be the basis of control line updating. The measurement points used are 100 mV, 1 V, 10 V, 100 V, and 1000 V. Over the year, there is no updating in the control line for 100 mV, 1 V, and 10 V because there is no out-of-control measurement result. Besides, there are 2 times control line updating for each 100 V and 1000 V because of artifact movement and drift. Even though it has been updated repeatedly, the last formed control line and the distribution of all data are still in the control line formed by the manufacturer's specifications.